Studies on synthesis, Raman, and electrical properties of novel spinel high entropy ceramics - Mishra, Rajesh K. [UNESP] (2024)
Entropy-stabilized ceramics have attracted researchers significantly due to their potential vast multi-functional applications in various engineering fields. The present study emphasizes the synthesis, sintering temperature, Raman, and electrical behavior of a spinel (CoAlFeNTi)3O4 high entropy oxide (HEO). The HEO is synthesized through the modified solid-state reaction method at two different sintering temperatures (1100 °C and 1250 °C) and characterized further with the XRD, Raman, and SEM for structural and microstructural behavior. XRD analysis confirmed the formation of a single cubic spinel phase with the Fd-3 m space group. In addition, Raman analysis also confirmed that the synthesized HEOs have a spinel structure with an inverse spinel nature. With the enhancement of the sintering temperature, XRD analysis indicates that the crystallinity and crystallite size of the HEO enhanced. The current density (J) versus applied electric field (E) characteristics displayed that both 1100 °C and 1250 °C sintered HEOs possessed leakage current density at zero applied electric field and an ohmic conductance of mhos/cm and mhos/cm respectively. Moreover, J - E characteristics also showed that the enhancement of sintering temperature enhanced the resistive switching behavior of the different temperature sintered spinel HEOs. This improved resistive switching behavior in the J-E curve indicates that the synthesized spinel HEO can find potential application in resistive switching memory devices.